The Role of Geography Education Lecturers in Measuring Students' Basic Literacy and Numeracy Skills at SDN Pujut District, Central Lombok Regency - Junaidin Junaidin; Siti Sanisah; Agus Herianto; Ravinesh Rohit Prasad (JURNAL GEOGRAFI, 2023)
The strategy to improve the quality of education in schools is to improve the management of literacy culture. Literacy refers to the process of reading, writing, and speaking to build, integrate, and critique meaning. Many researchers studied teachers' role in improving elementary school students' literacy and forgot how lecturers also have an essential role. This study aims to identify geography education lecturers' role in measuring students' basic literacy and numeracy skills at SDN Pujut District, Central Lombok Regency. Research Methods use descriptive qualitative. Interviews, observation, and descriptive analysis of documents by purposive sampling obtained data. To increase the credibility of research informants using the principle of data saturation. The results of this study show that students' literacy and numeracy skills are still low because teachers' ability in Central Lombok Regency is also considered to have decreased, so the support of parents is considered a servant. This research also shows that the role of geography education lecturers is very significant in measuring literacy and numeracy skills applied to all fields of learning in an integrated manner so that the roles of teachers and lecturers both have an essential role in measuring the literacy and numeracy of elementary school students.Keywords: Lecturer Role, Literacy Ability, Basic Numeracy of Students